谈美国华人：以近代影视视角看全球化下美国华人社会现象和成因 = The globalizing effect of the social phenomenon of American Chinese society in the cinematic environment - Tan, Samantha Li Ping (2015)
在世界多元化的大时代背景下，影视在传播各国文化和树立华人形象扮演着重要角色。从早期华人移民到美国，美国电影给华人贴上定型化标签如傅满洲、陈 查理、龙女等代表性华人形象。在全球化下，华人形象逐渐发生变化。随之出现受美国多元文化影响的“美国华人电影”开展新的探索与突破，重新制定美国华人社会现象。 全文以影视视角，从美国和中国角度为出发点，结合时代背景，依据三部近代美国华籍导演拍摄的“美国华人电影”来探讨在全球化下美国华人的社会现象和 成因，通过这些电影来分析中西文化的冲突与融合，和探究华裔的文化身份认同，后利用三部华人影视对比美国华人电影来看全球化在影视方面的运作，从而考察美 国华人电影是否刻板化华人在美国的社会现象，以及美国华人电影在全球化下的效 应和所产生的影响力。 Films play an important role in perpetuating one’s country culture and to create the images of Chinese. Since the arrival of early immigrants to America, we can see the negative portrayal of the representation of Chinese in American movies, perpetuating dehumanizing representations of the community, with the creation of stereotypical characters such as Dr. Fu Manchu, Charlie Chan, Dragon Lady. However, in today’s globalized context, coupled with the diversified culture, the images of Chinese have undergone a drastic change. The emergence of American-Chinese movies explores a new breakthrough, striving to change the stereotypical perception of American-Chinese. In this thesis, I seek to use television and movie films as a perspective, with America and China as my main focus, combining the backgrounds of the films, to explore the social phenomenon of American-Chinese society in a globalized context. In the first part of the paper, I will be using three American-Chinese movies to analyze the cultural differences and cohesion between the East and the West, and on the cultural identity of American-Chinese. In the second part of the paper, I will be doing a study by using three Chinese films as a comparison with American-Chinese movies, seeking to explore the aspects of the impact of globalization to films, to see if American-Chinese movies created a new social phenomenon of Chinese society, and to discuss how American-Chinese movies make an impact on the production of Chinese films.